Medical Theories on Malefic Possession: From Bewitchment to Anti-NMDAR Encephalitis - Uszkalo, Kirsten C. (Journal of religion in Europe, 2012)
Following a diagnostic trajectory that begins with early English cases of bewitchment and becomes hysteria, this article suggests that the new diagnostic category of anti-NMDAR encephalitis provides the best promise of finding a medical reason for the resiliency of some of the severe suffering allegedly caused by malefic possession in early modern England.